2008
DOI: 10.1111/j.1365-2435.2008.01385.x
|View full text |Cite
|
Sign up to set email alerts
|

Environmental signals for seed germination reflect habitat adaptations in four temperate Caryophyllaceae

Abstract: Summary 1.Requirements for dormancy break and seed germination are specific for all species and depend chiefly on phylogeny, geographical distribution, habitat preference and life cycle. Studying germination requirements of closely related species with a similar geographic distribution allows one to attribute variation in germination requirements to differences in habitat preference between the species. 2. We investigated requirements for dormancy break and the effect of environmental signals on induction of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
58
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(64 citation statements)
references
References 44 publications
4
58
1
1
Order By: Relevance
“…This is corroborated by the complete absence of light beyond the first mm in compact soils (Ciani et al 2005;Benvenuti 1995) when there are no soil cracks or aggregates (Burmeier et al 2010b). Light and response to diurnal fluctuating temperatures interact in their effect on germination (Vandelook et al 2008;Vincent and Roberts 1977), which complicates the picture for the shallowest soil layers.…”
Section: Introductionmentioning
confidence: 92%
“…This is corroborated by the complete absence of light beyond the first mm in compact soils (Ciani et al 2005;Benvenuti 1995) when there are no soil cracks or aggregates (Burmeier et al 2010b). Light and response to diurnal fluctuating temperatures interact in their effect on germination (Vandelook et al 2008;Vincent and Roberts 1977), which complicates the picture for the shallowest soil layers.…”
Section: Introductionmentioning
confidence: 92%
“…These results show that there is a high genotypic variability for the physiological parameters of germination in Cleome gynandra as the recent survey of Fredrick et al (2016) demonstrated in Faidherbia albida. Salt solutions and nitrogenous compounds have often been used to break the seed dormancy (Vandelook et al, 2008;Alboresi et al, 2005;Pérez-Fernandez and Rodriguez-Echeverria, 2003;Bell et al, 1999;Hendricks and Taylorson, 1972;Mayer and PolkjaoffMayber, 1963). In the present study, we used 2 and 5 gL -1 of KNO 3 .…”
Section: Discussionmentioning
confidence: 99%
“…Many post-dispersal factors can have profound influence on recruitment (Roberts & Heithaus 1986;Schupp 1990;Howe 1993;Shepherd & Chapman 1998) including environmental conditions such as temperature, radiation, and water availability that greatly infl uence the development of the embryonic axis during germination (Carvalho & Nakagawa 2000;Vandelook et al 2008;Baskin & Baskin 2014), and seed predation (Janzen 1971;Howe & Smallwood 1982;Schupp 1990). Dealing with unfavorable environmental conditions (Hölzel & Otte 2004) and escaping predation often involve mutualistic interactions, such as long seed dispersal away from the mother plant (Janzen 1970;Wicklow et al 1984;Estrada & Coates-Estrada 1991;Comita et al 2014).…”
Section: Introductionmentioning
confidence: 99%